# help math

posted by .

solve each of the following quadratic equation
(1)x^2=5x+6
(2)x^2+9x=10

• help math -

Find factors of the end terms that will sum to the middle term.

1. x^2 - 5x - 6 = 0 = (x+1)(x-6)

x = 6 or -1

I'll leave the second equation to you.

## Similar Questions

1. ### Algebra2

Find the polynomials roots to each of the following problems: #1) x^2+3x+1 #2) x^2+4x+3=0 #3) -2x^2+4x-5 #3 is not an equation. Dod you omit "= 0" at the end?
2. ### Math

Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand about …

Hi, I am trying to solve graphing quadratic equations. One of the problems is written as -x^2= -2x-1. So if I wanted to put this equation in the proper quadratic equation form, would it be -2x-1-x^2, or -x^2+-2x-1?
4. ### algebra II

I'm quite clueless as to how to solve this. I know the quadratic equation but am not sure how to get this equation into the format to plug in to the quadratic... Solve the quadratic equation using the formula [1/(1+x)]-[1/(3-x)]=(6/35) …
5. ### algebra

which quadratic formula would be used to solve the following quadratic equation?
6. ### algebra

0. Tell your classmates about your pet to set up the scenario for fencing a rectangle in your yard. 1. You MUST start by choosing an amount of area that you want to fence in for your pet and this MUST be stated first. What amount of …